A STUDY OF EXERCISE HABITS AND EXERCISE RATE IN ELDERLY WREDHA RINDANG ASIH - Habiburrahman, Fauzan Asa; Setiowati, Anies (Sports Medicine Curiosity Journal, 2022)
Physical activity is one of the most important efforts to maintain and improve health. In achieving the needs of daily activities, every elderly can do exercise habits. Someone with low physical activity habits (sedentary) has a higher risk of experiencing health problems. The purpose of this study was to describe the level of exercise habits and intensity of exercise in the elderly. The research method uses a quantitative approach with a survey type that aims to investigate whether there is a relationship between the independent variable and the dependent variable. The population of the research sample is the elderly at Panti Wredha Rindang Asih, a sample of 28 people with purposive sampling technique consisting of 16 men and 12 women. Data were collected by filling out questionnaires and measuring resting pulse in the morning and measuring exercise pulse after participating in physical training (gymnastics). The results of the study of exercise habits showed 19 elderly people (67.87%) were in the good category. The results of the measurement of resting pulse showed that 28 elderly people (100%) were in the normal category (60-100x/minute). The results of the exercise pulse measurement showed that 21 people (75%) were in the normal category, there was an increase in the elderly's pulse rate of 24% with an average pulse rate (98.6x/minute). The conclusion of this study is that the level of exercise habits in the elderly is in the good category, while the intensity level of exercise in the elderly is in the medium category. There is no relationship between exercise habits and exercise rate in the elderly at Panti Wredha Rindang Asih. Suggestions for the elderly to always maintain exercise habits by getting used to a healthy life and regular exercise.